1996
DOI: 10.1111/j.1365-2478.1996.tb00174.x
|View full text |Cite
|
Sign up to set email alerts
|

The magnetotelluric response over 2D media with resistivity frequency dispersion1

Abstract: We investigate the magnetotelluric response of two-dimensional bodies, characterized by the presence of low-frequency dispersion phenomena of the electrical parameters. The Cole-Cole dispersion model is assumed to represent the frequency dependence of the 'impedivity' complex function, defined as the inverse of Stoyer's 'admittivity' complex parameter. To simulate real geological situations, we consider three structural models, representing a sedimentary basin, a geothermal system and a magma chamber, assumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Following the theory developed by Patella (1987Patella ( , 1993, the CC model has been included in the magnetotelluric (MT) method to study the distortions provoked by IP on 1D (Di Maio et al, 1991) and 2D (Mauriello et al, 1996) synthetic responses. IP effects in MT have been experimentally recognized in volcanic and geothermal areas (Patella et al, 1991;Coppola et al, 1993;Giammetti et al, 1996;Di Maio et al, 1997Mauriello et al, 2000Mauriello et al, , 2004.…”
Section: Puttingmentioning
confidence: 99%
“…Following the theory developed by Patella (1987Patella ( , 1993, the CC model has been included in the magnetotelluric (MT) method to study the distortions provoked by IP on 1D (Di Maio et al, 1991) and 2D (Mauriello et al, 1996) synthetic responses. IP effects in MT have been experimentally recognized in volcanic and geothermal areas (Patella et al, 1991;Coppola et al, 1993;Giammetti et al, 1996;Di Maio et al, 1997Mauriello et al, 2000Mauriello et al, , 2004.…”
Section: Puttingmentioning
confidence: 99%
“…This a slightly different representation compared with that used in classical not dispersive MT, where the phase curves of the wave impedance are generally drawn, e.g., [42]. Using the well known relationship between apparent impedivity and wave impedance, e.g., [19,24,42], it can be easily demonstrated that the apparent impedivity phase function is equal to two times the impedance phase function minus 90 • .…”
Section: The Mt Response In Presence Of Dispersionmentioning
confidence: 99%
“…Following the theory developed by [23,24], the Cole-Cole model was included in MT to study the distortions provoked by dispersion on 1D [8] and 2D [19] synthetic responses. Positive dispersion effects in MT were experimentally recognized in volcanic and geothermal areas [6,9,10,12,20,21,27].…”
Section: Introductionmentioning
confidence: 99%
“…A generalized Ohm's law J(t)=σ*e(t) has been used in geophysics to model electromagnetic induction in a polarizable medium [Esposito et al 2017, Mauriello et al 1996, Patella 2008, Smith et al 1988. Typically, modelling EM induction in such a medium is performed in the frequency domain, in which case Ohm's law becomes the product J(ω)=σ(ω)E(ω), and the governing Maxwell equations are solved for a given frequency assuming a time-harmonic source excitation.…”
Section: Principles Of the Central Loop Transient Electromagnetic Metmentioning
confidence: 99%